In connection with the publication in Bali Med J 2016, Volume 5, Number 2: 25-29, entitled "Intra-Arterial Heparin Flushing Increases Manual Muscle Test – Medical Research Councils (MMT-MRC) Score in Chronic Ischemic Stroke Patient " - Machfoed, Moh Hasan; Usman, Fritz Sumantri; Barus, Jimmy; Wreksoatmodjo, Budi Riyanto; Gunawan, Dede; Bintang, Andi Kurnia; Tugasworo, Dodik; Subroto, Gatot; Lamsudin, Rusdi; Harsono, H.; Sulthan, Riza (BALI MEDICAL JOURNAL; Vol 5 No 2 (2016), 2016)
In connection with the publication in Bali Med J 2016, Volume 5, Number 2: 25-29, entitled "Intra-Arterial Heparin Flushing Increases Manual Muscle Test – Medical Research Councils (MMT-MRC) Score in Chronic Ischemic Stroke Patient ", herewith, please allow us to do reviews of the study discussion. By assessing the discussion, it can be proved whether there are references that support the results of study.